Unraveling Nanostructured Spin Textures in Bulk Magnets. Issue 1 (6th September 2020) - Bender, Philipp; Leliaert, Jonathan; Bersweiler, Mathias; Honecker, Dirk; Michels, Andreas
Abstract : One of the key challenges in magnetism remains the determination of the nanoscopic magnetization profile within the volume of thick samples, such as permanent ferromagnets. Thanks to the large penetration depth of neutrons, magnetic small‐angle neutron scattering (SANS) is a powerful technique to characterize bulk samples. The major challenge regarding magnetic SANS is accessing the real‐space magnetization vector field from the reciprocal scattering data. In this study, a fast iterative algorithm is introduced that allows one to extract the underlying 2D magnetic correlation functions from the scattering patterns. This approach is used here to analyze the magnetic microstructure of Nanoperm, a nanocrystalline alloy which is widely used in power electronics due to its extraordinary soft magnetic properties. It can be shown that the computed correlation functions clearly reflect the projection of the 3D magnetization vector field onto the detector plane, which demonstrates that the used methodology can be applied to probe directly spin textures within bulk samples with nanometer resolution. Abstract : A fast iterative algorithm is introduced to extract the 2D magnetic correlation functions from magnetic small‐angle neutron scattering patterns. This approach is used to probe the nanoscopic spin textures within the nanostructured soft magnetic alloy Nanoperm. By comparing the results with micromagnetic simulations and theoretical calculations, it can be verified that the extracted correlation functions reflect the real‐space magnetization distribution.